A novel reassortant strain of the infectious bursal disease virus (IBDV ASPVB) from Iraqi broiler farms: A first-time molecular and histopathological investigation revealing new insights. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The objective of this investigation was to identify and detect the reassortant infectious bursal disease virus (IBDV) strain from broiler farms suspected of being infected. Materials and Methods: The broiler yielded 72 samples, including the spleen and bursa of Fabricius. The tissues underwent histological examination before being used in a typical PCR molecular investigation. Results: The strain was subsequently termed IBDV ASPVB. The IBDV ASPVB strain in Iraq has been identified as a novel reassortant strain based on the results of PCR, sequencing, and phylogenetic analysis of partial segments A and B. Segment A of this strain is derived from the highly pathogenic IBDV strain. In contrast, segment B is derived from other field reassortant strains. Infection with this strain might result in minor clinical symptoms but substantial damage to lymphoid organs, leading to compromised immunological responses. Conclusion: As a result of ongoing evolution, this study demonstrates that IBDV in Iraq exhibits a wide range of histological, genetic, and phenotypic variation; to our knowledge, this paper represents the first report of reassortant IBDV in Iraq. J. Adv. Vet. Anim. Res., 12(2): 385–395, June 2025http://doi.org/10.5455/javar.2025.l906